Answer:
g + h = 6
Explanation:
We are told that:
•
![g + 9 = 4](https://img.qammunity.org/2023/formulas/mathematics/high-school/4amuwzf7b6v58sddcsvzwof7bwpc70nisz.png)
•
.
To calculate the value of g + h, we have to rearrange the above equations to make g and h their respective subjects:
•
![g + 9 = 4](https://img.qammunity.org/2023/formulas/mathematics/high-school/4amuwzf7b6v58sddcsvzwof7bwpc70nisz.png)
⇒
[Subtracting 9 from both sides]
⇒
![g = \bf -5](https://img.qammunity.org/2023/formulas/mathematics/high-school/9zse6kfkpgf29ylih74j44veqldyb3zlh9.png)
•
![h- 8=3](https://img.qammunity.org/2023/formulas/mathematics/high-school/agcp9abed8issm2y7xpb1hqv2zfghw5mlk.png)
⇒
[Adding 8 to both sides]
⇒
![h = \bf 11](https://img.qammunity.org/2023/formulas/mathematics/high-school/41zdthp3uzkot4vrkiq3lse1nq664zt8h4.png)
Now that we know the values of g and h, we can find the value of g + h:
![g + h](https://img.qammunity.org/2023/formulas/mathematics/high-school/qmtdnbacn2b8pvdy4a7yicg0zhyq47svil.png)
![= -5 + 11](https://img.qammunity.org/2023/formulas/mathematics/high-school/xz8gy15jn6lwn21u6evl2zntajida4rfnq.png)
![= \bf 6](https://img.qammunity.org/2023/formulas/mathematics/high-school/9iiimpbjo6r1kifwbbwq33r7xcy2o5ra3z.png)
Therefore the value of g + h is 6.